2014
DOI: 10.1371/journal.pone.0108361
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Robotic Surgery with Laparoscopy and Laparotomy for Treatment of Endometrial Cancer: A Meta-Analysis

Abstract: PurposeTo compare the relative merits among robotic surgery, laparoscopy, and laparotomy for patients with endometrial cancer by conducting a meta-analysis.MethodsThe MEDLINE, Embase, PubMed, Web of Science, and Cochrane Library databases were searched. Studies clearly documenting a comparison between robotic surgery and laparoscopy or between robotic surgery and laparotomy for endometrial cancer were selected. The outcome measures included operating time (OT), number of complications, length of hospital stay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 31 publications
(58 reference statements)
6
48
4
2
Order By: Relevance
“…In contrast to our study, in a meta-analysis involving 3403 patients, Ran L et al 10 reported shorter operative time and lower blood loss, but higher complication rates in robotic surgery than laparoscopy. Moreover, in the meta-analysis of Ran L et al 10 the hospital stay and transfusion rates were equivalent in robotic surgery and laparoscopy. Instead, in our study, hospital stay was shorter in robotic group than in laparoscopy group (Table 2), but this result could be linked to the higher complication rates that we obtained in laparoscopy Group (Table 3).…”
Section: Surgical Outcomecontrasting
confidence: 99%
“…In contrast to our study, in a meta-analysis involving 3403 patients, Ran L et al 10 reported shorter operative time and lower blood loss, but higher complication rates in robotic surgery than laparoscopy. Moreover, in the meta-analysis of Ran L et al 10 the hospital stay and transfusion rates were equivalent in robotic surgery and laparoscopy. Instead, in our study, hospital stay was shorter in robotic group than in laparoscopy group (Table 2), but this result could be linked to the higher complication rates that we obtained in laparoscopy Group (Table 3).…”
Section: Surgical Outcomecontrasting
confidence: 99%
“…Interestingly, in the Chicago group's study 10, the cold ischemia time was 47 min longer in the robotic group than the open surgery group. Based on our experience and the results of large meta‐analyses and series, the use of robotic assistance is likely responsible for an increase in operative time, as compared to open or laparoscopic surgery 17, 18, 19, 20, 21. We thus believe that a longer anastomosis time and uncontrolled kidney rewarming are valid concerns in robot‐assisted kidney transplantation.…”
Section: Discussionmentioning
confidence: 95%
“…In a metaanalysis of patients undergoing surgery for endometrial cancer, TLH was associated with a higher complication rate compared to RALH although the absolute numbers of events in both groups were low. 4 A meta-analysis of 26 non-randomised studies that included more than 4000 patients with early stage cervical cancer showed that perioperative outcomes were no different between RALH and TLH. 16 In the current study, there were no observed differences between the RALH and TLH groups in post-operative pain at 24 h, or the use of opioid analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…3 Retrospective studies suggest that in patients with endometrial cancers RALH may be associated with a shorter hospital stay, less blood loss and fewer complications compared to TLH. 4 However, in women with benign disease, RALH has not been shown to improve outcomes and is associated with longer operating times and higher cost compared to TLH. 5 The American…”
Section: Introductionmentioning
confidence: 99%